Bin Tcheek, Abdul Rahman. “Prospects of Teaching Arabic Language and its Obstacles in South-East Asia,” Year 3, Issue 12 (Spring 1418-1419 AH/ 1998 CE), Pp. 159-190. - بن تشيك, عبد الرحمن (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1998)
Abdul Rahman Bin Tcheek describes the region of South-East Asia and the Arabic language in general, then focuses on the prospects of teaching Arabic in Indonesia, Malaysia, Brunei, Philippines, Singapore, and Thailand. He addresses the obstacles in the way of teaching Arabic there, citing civilizational challenges, vocalization (enunciation) variances, geographic distance from the Arab world, absence of an Arab environment, and the scarcity of specialists in teaching the language and its sciences. Bin Tcheek recommends further attention on this matter and cooperation through providing material support, building educational and cultural centers, and specialized institutions to train instructors in teaching Arabic to Southeast Asian Muslims.